2013
DOI: 10.1590/brag.2013.036
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos bioquímicos da resistência do algodoeiro à ramulose potencializada pelo silício

Abstract: ResumoObjetivou-se avaliar o efeito do silício (Si) sobre a ramulose e aspectos bioquímicos da resistência do algodoeiro a essa doença. Os cultivares BRS Araçá e FM 993 foram desenvolvidos em solução nutritiva contendo (+Si) ou não (-Si) silício. Avaliou-se o período de incubação (PI), incidência (I), área abaixo da curva do índice da ramulose (AACIR) e concentração foliar de Si (CFSi).A CFSi e o PI aumentaram em 76% e 19,5%, respectivamente, nas plantas +Si em relação às -Si, e a I e a AACIR diminuíram em 64%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
(24 reference statements)
0
4
0
2
Order By: Relevance
“…The PPO participates in the oxidation of phenolics leading to the production of quinones, which are extremely toxic to many pathogens (Campbell and Sederoff 1996). Guerra et al (2013) and Liang et al (2005) reported that Si potentiated the resistance to ramulosis and powdery mildew in cotton and cucumber, respectively, through an increase in the activities of POX and PPO that stimulated the accumulation of phenolic compounds. Tatagiba et al (2014) reported that high concentrations of soluble phenolics (SP) (hbi) with X. oryzae pv.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The PPO participates in the oxidation of phenolics leading to the production of quinones, which are extremely toxic to many pathogens (Campbell and Sederoff 1996). Guerra et al (2013) and Liang et al (2005) reported that Si potentiated the resistance to ramulosis and powdery mildew in cotton and cucumber, respectively, through an increase in the activities of POX and PPO that stimulated the accumulation of phenolic compounds. Tatagiba et al (2014) reported that high concentrations of soluble phenolics (SP) (hbi) with X. oryzae pv.…”
Section: Discussionmentioning
confidence: 99%
“…The Si-mediated plant resistance to pathogens has been attributed to an increase in the density of the long and short silicate cells in the leaf epidermis or the existence of a thick silica layer below the cuticle that forms a physical barrier which prevents or slows fungal penetration (Hayasaka et al 2008;Kim et al 2002). Furthermore, increases in the concentrations of soluble phenolics, lignin, and phytoalexins, an enhanced activity of defense-related enzymes, and the fast and strong transcription of genes that are related to host defense against pathogens are the reported biochemical mechanisms that are potentiated by Si in plants infected by pathogens (Guerra et al 2013;Liang et al 2005;Rodrigues et al 2003Rodrigues et al , 2004Rodrigues et al , 2005Tatagiba et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A atividade da QUI (EC 3.2.1.14) foi determinada por meio da quantificação colorimétrica da liberação de "pnitrophenyl" clivado do substrato análogo da quitina "p-nitrophenyl-β-D-N,N'diacetylchitobiose"(PNP) (Sigma-Aldrich, São Paulo, Brasil) e expressa em mM de "p-nitrophenyl" produzido por min -1 mg -1 de proteína. A atividade da enzima fenilalanina amônia-liase (FAL, EC 4.3.1.5) foi quantificada conforme descrito em Guerra et al (12), baseado na quantificação calorimétrica do ácido trans-cinâmico liberado do substrato fenilalanina (Sigma-Aldrich, São Paulo, Brasil) e expressa em μmol de ácido trans cinâmico min -1 mg -1 de proteína. A concentração de proteínas utilizada para o cálculo da atividade das enzimas foi obtida pelo método de Bradford, usando albumina sérica bovina como padrão.…”
Section: Methodsunclassified